Clusters as a vehicle for regional development - The case of Lublin Region - Ewa Bojar; Matylda Bojar (European Regional Science Association (ERSA), 2011)
Clusters are a specific form of spatial organization of various sectors of industry and services regarded as the most mature form of organization of production in the post-industrial era. Research on existing cluster structures clearly demonstrates that clusters can be an important drive of regional development. Clusters have positive influence on the other sectors of local and regional economy and significantly contribute to the development of their international competitive advantage. The clusters through external effects, such as technological spill-over, affect the other sectors of local and regional economy and thus lead to increasing their international competitive advantage. Even the cluster-like structures by many are viewed as stimulators of regional development capable to contribute significantly to the growth of export and attract considerable amounts of foreign investments. Cooperation within the cluster structures can produce a wide array of synergy effects and thus cluster participants can benefit even more. Cooperation within the framework of clusters is particularly advantageous to small and medium-sized enterprises; they can combine their innovative potential, team up and apply for external funds more effectively. The concept of clusters represents an important step towards explaining the reasons for unequal distribution of economic activities in space and resultant disparities in economic development between various regions. A groundbreaking model of clusters based on the triple helix of science, business and government has determined new approach to stimulating innovation in order to alleviate regional disparities and ensure sustainable hi-tech regional development. The paper explores clusters as a crucial concept in modern management and contemporary economic development theories and discusses selected factors shaping clustering processes.
Keywords: 330